STUDI DESAIN DOWN SCALE TERAS REAKTOR DAN BAHAN BAKAR PLTN JENIS PEBBLE BED MODULAR REACTOR – HTR 100 MWE - Parmanto, Slamet; Widiharto, Andang; Sardjono, Yohannes (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
Research of Pebble Bed Modular Reactor (PBMR) 100 MWe which used UO2 fuel has been done. This reactor uses graphite as moderator and helium as coolant. Down scale studies performed without changing the core and fuel geometry. The parameter being analyzed were core criticality, excess reactivity, fuel, moderator, coolant temperature reactivity coefficient, and fuel economy. This research is expected to obtain the design that has fuel economy and inherent safety features. In this research, we have employed SRAC 2003 code. The calculation show that the UO2 pebble fuel design with 10% enrichment of U235 and 90 ppm burnable poison of Gd2O3 results in the effective multiplication factor (keff) value of 1,01115 at beginning of life (BOL) and become 1,00588 after 2658 days of reactor operation. The core temperature reactivity coefficient is -3.25900E-05 ∆k/k/K and -1,100615E-04 ∆k/k/K at BOL and end of life (EOL), respectively. The reactor is in compliance with inherent safety characteristics indicated by the value of a negative temperature reactivity coefficient.